PENANAMAN NILAI-NILAI KEAGAMAAN UNTUK PENINGKATAN RELIGIUSITAS ANAK ANAK BERKEBUTUHAN KHUSUS - Eka Dheasari, Agustiarini; Muhammad, Devy Habibi; Atus Soliha, Imro (LPPM STAI Muhammadiyah Probolinggo, 2024)
Cultivation of religious values religious values is one of the important steps to improve the religiosity of Children with Special Needs (ABK). This community service program aims to help children with disabilities at the Ananda Mutiara Indonesia Foundation, Probolinggo Branch in understanding, appreciating, and practicing religious values. Activities activities are carried out with the approach of habituation, exemplary, storytelling, and positive reinforcement, which are designed according to the conditions and conditions of the children. designed according to the child's conditions and needs. Results results show that intensive cultivation of religious values can improve the religiosity of children with disabilities, which can be seen from positive behavioral changes, increased awareness of worship, and children's ability to behavior, increased awareness of worship, and children's ability to apply religious values in daily life apply religious values in daily life. This program also increased the awareness of parents and the community about the importance of their role in supporting the spiritual development of children with disabilities. In supporting the spiritual development of children with disabilities. This service is expected to be an effective first step in building the religiosity of children with disabilities in a sustainable way and help them lead more meaningful lives in an inclusive social environment. inclusive social environment.